Building Students' Critical Thinking Skills Through the Development of Teaching Materials Based on Integration, Interconnection, and Research Based Learning - Sutarto (Institute of Computer Science (IOCS), 2022)
Critical thinking has a critical role for every individual in facing global challenges. However, only some can develop critical thinking skills. This qualitative research with a phenomenological approach aims to explore the experience of lecturers of the Postgraduate Islamic Education Study Program at IAIN Curup in developing students' critical thinking skills. The research informants amounted to 8 people. Data were collected using semi-structured interviews, then analyzed using the Miles and Huberman analysis model. The data validity technique used is source triangulation and interview extension. The results showed that the development of integration-based and interconnection-based teaching materials to develop students' critical thinking skills was carried out through four levels: philosophical, material, methodological, and strategy. In contrast, research-based learning is carried out by giving mini-research assignments to students. The results of the mini-research were analyzed from various perspectives and presented for academic accountability.